Asian and Global Financial Crises' Effect on Malaysia Co2 Emission - Bakhtyar, B. (International Journal of Energy Economics and Policy, 2017)
Malaysian economy has experienced two financial crises in less than 12 years. The Asian financial crisis started in Thailand on July 1997, which intensively affected the Malaysian Ringgit within days. The rate of the Malaysian Gross Domestic Product (GDP) dropped to -7.36 at its nadir in 1998. In 2008, the global financial crisis hit Western countries and rapidly affected the economic growth of Malaysia. The GDP growth decreased by 0.1% in the last quarter of 2008, and reached -1.51 in a particular situation in 2009. Through a qualitative analysis, this paper investigates the CO2 emission during these financial crises by focusing on three main fuel CO2 emission, namely, coal, natural gas, and petroleum. This study shows that the rate of CO2 emission growth in Malaysia decreased despite the negative GDP during both crises, but the carbon emission trend did not decline. Keywords: CO2 emission, gross domestic product (GDP), global financial crisis (GFC), Asian financial crisis (AFC) JEL Classifications: G01, Q43